PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS DISCOVERY LEARNING PADA MATERI VEKTOR PESERTA DIDIK KELAS X SMA KPG KHAS “PAPUA” MERAUKE - ROSALINA ESTI LESTARI; VIRMAN VIRMAN (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This research is a research and development (Research & Development) which aims to find out how to develop physics learning module based on discovery learning on vector material of class X students of SMA KPG Typical